2014
DOI: 10.1177/1077695814551833
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Effects of Citizen Journalism Practice on College Students’ Social Capital

Abstract: This study examined the effects of citizen journalism practices on social capital concerning nonprofit and voluntary organizations (i.e., satisfaction, trust, and engagement). Through a quasi-experimental design, the analyses revealed that students in the treatment group, in which participants engaged in citizen journalism practice, had greater positive changes in levels of satisfaction, trust, and engagement than students in the control group. This study offers unique contributions to the existing body of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These responses were often directly framed within the context of technology, where participants claimed that technology gave them a greater sense of voice and local knowledge. Nah et al (2014) found similar results in their study of college students who participated in citizen journalism, finding a significant increase in community engagement, social capital, and civic education.…”
Section: Understanding Community Connection Through Technologysupporting
confidence: 58%
“…These responses were often directly framed within the context of technology, where participants claimed that technology gave them a greater sense of voice and local knowledge. Nah et al (2014) found similar results in their study of college students who participated in citizen journalism, finding a significant increase in community engagement, social capital, and civic education.…”
Section: Understanding Community Connection Through Technologysupporting
confidence: 58%
“…We conducted the study using a quasi-experimental design with nonequivalent groups , which are typical in educational settings that do not allow for randomization (Mark & Reichardt, 1998). “The quasi-experimental design is appropriate in that it mirrors conditions under which the intervention could be implemented in college communication courses, which would occur at the course (not individual) level” (Nah, Namkoong, Van Stee, & Record, 2014, p. 372). Quasi-experiments can have high internal validity (Rubin & Babbie, 2011) and are less expensive than experiments, but lack randomization.…”
Section: Methodsmentioning
confidence: 99%
“…After an instructional program that helped journalism students compare civic journalism with traditional journalism, Anyaegbunam and Ryan (2003) found that students became slightly more favorable toward interacting with readers. Similarly, Nah et al (2014) found that students practicing citizen journalism gained trust, satisfaction and engagement.…”
Section: Literature Reviewmentioning
confidence: 96%